Outcome of transplantation for acute lymphoblastic leukemia in children with down syndrome. Issue 6 (4th January 2014) - Hitzler, Johann K.; He, Wensheng; Doyle, John; Cairo, Mitchell; Camitta, Bruce M.; Chan, Ka Wah; Perez, Miguel A. Diaz; Fraser, Christopher; Gross, Thomas G.; Horan, John T.; Kennedy‐Nasser, Alana A.; Kitko, Carrie; et al.
<x xml:space="preserve">Abstract</x> We report on 27 patients with Down syndrome (DS) and acute lymphoblastic leukemia (ALL) who received allogeneic hematopoietic cell transplantation (HCT) between 2000 and 2009. Seventy‐eight percent of patients received myeloablative conditioning and 52% underwent transplantation in second remission. Disease‐free survival (DFS) was 24% at a median of 3 years. Post‐transplant leukemic relapse was more frequent than expected for children with DS‐ALL (54%) than for non‐DS ALL. These data suggest leukemic relapse rather than transplant toxicity is the most important cause of treatment failure. Advancements in leukemia control are especially needed for improvement in HCT outcomes for DS‐ALL. Pediatr Blood Cancer 2014;61:1126–1128. © 2014 Wiley Periodicals, Inc.